Pollen grain morphology supports the taxonomical discrimination of Mediterranean oaks (Quercus, Fagaceae) - Colombo, P M; Lorenzoni, F C; Grigoletto, F (Plant Systematics and Evolution, 1983)
The exine architecture and some quantitative parameters (polar and equatorial axes and their ratio) of pollen grains allow a clear discrimination between groups of Mediterranean oak species. For the differentiation of species within groups only the quoted parameters prove useful.
Keywords: Angiosperms; Fagaceae; Pollen exine architecture; pollen grain size and form; Quercus